Preparation and Characterization of Site-Specific Fatty Chain-Modified Recombinant Human Granulocyte Colony Stimulating Factor - Wang, Xu-Dong; Yu, Wei-Jia; Liu, Jia-Hui; Du, Jie; Chen, Kang-Nan; Hu, Qin-Qin; Sun, Wen-Long; Ying, Guo-Qing (Frontiers in Bioengineering and Biotechnology, 2022)
The clinical use of recombinant human granulocyte colony-stimulating factor (rhG-CSF) is limited by its short serum half-life. In this study, a long-acting strategy for site-specific modification of rhG-CSF with 1-pentadecyl-1H-pyrrole-2,5-dione (C15 fatty chain-maleimide, C15-MAL) was studied in mixed DMSO-aqueous solutions. The factors influencing the conjugation reaction were investigated and optimized, and a high yield of the desired product (C15-rhG-CSF) was achieved. Subsequently, C15-rhG-CSF product was eﬃciently purified using preparative liquid chromatography, and further characterized. Circular dichroism spectroscopy analysis showed that the secondary structure of C15-rhG-CSF had no significant difference from unmodified rhG-CSF. C15-rhG-CSF retained 87.2% of in vitro bioactivity of unmodified rhG-CSF. The pharmacokinetic study showed that the serum half-life of C15-rhG-CSF in mice was 2.08-fold longer than that of unmodified rhG-CSF. Furthermore, C15-rhG-CSF by single-dose subcutaneous administration showed better in vivo efficacy than those of both PEG10k-rhG-CSF by single-dose administration and rhG-CSF by multiple doses administration. This study demonstrated the potential of C15-rhG-CSF being developed into a novel drug candidate as well as an efficient process for the development of long-acting protein and peptide drugs.